THE ROLE OF TURKISH ISLAMIC UNION FOR RELIGIOUS AFFAIR )DITIB) IN TERMINATING THE DISCRIMINATION ON "IDENTITY AND CULTURE" OF TURKISH MOSLEM IN GERMANY (1984-2009) - Ivan Patria (Universitas Muhammadiyah Yogyakarta, 2011)
THE ROLE OF TURKISH ISLAMIC UNION FOR RELIGIOUS AFFAIR )DITIB) IN TERMINATING THE DISCRIMINATION ON "IDENTITY AND CULTURE" OF TURKISH MOSLEM IN GERMANY (1984-2009)